The “Evolution” of Regulation in Uganda’s Mobile Money Sector - Rory Macmillan; Anthea Paelo; Tamara Paremoer (The African Journal of Information and Communication, 2016)
Uganda’s mobile money sector has grown rapidly since its introduction in 2009. As at the last quarter of 2015, there were 21.1 million registered mobile money users in the country, representing a penetration of about 54%. As well as providing a convenient, cheap and safe means of money transfer, mobile money has spurred increased financial inclusion, which grew from 28% in 2009 to 54% in 2013. The rapid growth has happened under conditions of “light touch” regulation of the sector, which allows the first mover to reap the rewards of investments made, but raises potential competition issues. The mobile money sector, much like the telecommunications sector, is characterised by network externalities, lock-in effects and high barriers to entry that can give rise to a concentrated sector with a single dominant player. This article considers the effect of light touch regulation on the competitive dynamics in the mobile money market in Uganda and contrasts this with the experience in Tanzania, where regulation evolved from a light touch style to a more comprehensive framework as the sector grew.